Pengaruh Kepribadian Merek, Pengalaman Merek, dan Cinta Merek The Body Shop terhadap Loyalitas Merek - Cici Cici; Rahayu Mardikaningsih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
There are various kinds of companies engaged in the field of care and beauty, considering the increasing demand for women's care. Competing with various product advantages, various types of products, and quality does not make The Body Shop lose consumers. Established since 1976 until now, The Body Shop has had its own place in the minds of consumers, by creating beauty and care products made from herbal, environmentally friendly, safe for skin and body. The purpose of this study is to test whether brand personality, brand experience, and brand love affect brand loyalty to The Body Shop consumers. This study was tested using multiple linear regression analysis techniques, with a sample of 100 consumers of The Body Shop. This study proves that brand loyalty has a significant effect on brand personality, brand experience, and brand love. Brand experience is proven to have an effect on brand loyalty. In addition, brand loyalty is also significantly influenced by brand love